Optimalisasi Keterampilan Berpikir Kritis Mahasiswa Melalui Sekolah Legislasi Senat Mahasiswa - Rohman, Akhmad Dalil; Novitasari, Ririn (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
In facing the demands of an increasingly complex era of globalization, critical thinking skills are an important aspect for students in improving their analysis, evaluation and problem solving skills. UIN FTIK Student Senate K.H. Abdurrahman Wahid Pekalongan realized the importance of developing critical thinking skills and introduced the Legislation School program. Through an approach of presenting material, discussion and argumentative debate, this program aims to optimize student potential in developing critical thinking skills effectively. The research results show that the Legislation School program has had a significant positive impact in improving the critical thinking skills of FTIK UIN K.H. students. Abdurrahman Wahid Pekalongan. Participants demonstrated increased ability to analyze information, identify logical arguments, and evaluate opinions critically. This program has proven to be an effective solution for improving students' critical thinking skills in a college environment. In conclusion, the Legislation School program with an approach to presenting material, discussion and argumentative debate succeeded in optimizing the critical thinking skills of FTIK UIN K.H. students. Abdurrahman Wahid Pekalongan. These findings emphasize the importance of a structured approach in improving critical thinking skills in higher education. The integration of similar programs in the curriculum is expected to improve the quality of higher education and prepare students to face global challenges in the future.